Respuesta :
Answer:
m=18+n
Step-by-step explanation:
m + -18 = n simplify
-18 + m = n record the terms
-18 + 18 + m = 18 + n solve
Combine like terms: -18 + 18 = 0, 0 + m = 18 + n, m = 18 + n
Final answer: m = 18 + n
Answer:
IDK but here's what I have found.....
Step-by-step explanation:
Simplifying
m + -18 = n
Reorder the terms:
-18 + m = n
Solving
-18 + m = n
Solving for variable 'm'.
Move all terms containing m to the left, all other terms to the right.
Add '18' to each side of the equation.
-18 + 18 + m = 18 + n
Combine like terms: -18 + 18 = 0
0 + m = 18 + n
m = 18 + n
Simplifying
m = 18 + n